Technical evaluation of the IBOC and DRM digital broadcasting standards for implementation in the city of Cali, Colombia - Miranda, Lennin
Currently, Colombia operates the analog terrestrial radio broadcasting system. There are more than 1,700 stations in our country; among these there are commercial, community and other public interest stations. Likewise, in this transmission medium there are different needs identified such as the inadequate use of the radio spectrum in the regions due to the ease of setting up transmitters, the number of stations added to the requests for broadcasting licenses for new stations. This study was focused on the city of Cali, where the phenomenon of informal stations occurs. According to the MINTIC, more than 30 of them emit their signal, causing great interference to the medium. Through this research, the transmission of digital sound broadcasting is analyzed as an alternative to the solution of the problems currently presented. In this sense, the digital broadcasting standards IBOC (In Band On Channel) and DRM (Digital Radio Mondiale) were evaluated, through the comparison of their technical characteristics and the simulation of these in the city of CALI. The simulations carried out in XIRIO are presented, where the 2 standards were evaluated independently. To do this, 18 real stations from the city of Cali were configured in the FM band, covering frequencies from 88.5 to 107.5 MHz. Additionally, 4 stations from nearby municipalities were included to simulate possible interferences. Subsequently, the multi-coverage and interference study was executed, taking 22 reference points to capture data on coordinates, power reception levels and signal quality.